Brevicoryne brassicae aphids interfere with transcriptome responses of Arabidopsis thaliana to feeding by Plutella xylostella caterpillars in a density‑dependent manner - Kroes, Anneke; Broekgaarden, Colette; Castellanos Uribe, Marcos; May, Sean; van Loon, Joop J.A.; Dicke, Marcel (Springer, 2017)
Plants are commonly attacked by multiple herbivorous species. Yet, little is known about transcriptional patterns underlying plant responses to multiple insect attackers feeding simultaneously. Here, we assessed= transcriptomic responses of Arabidopsis thaliana plants to simultaneous feeding by Plutella xylostella caterpillars and Brevicoryne brassicae aphids in comparison to plants infested by P. xylostella caterpillars alone, using microarray analysis. We particularly investigated how aphid feeding interferes with the transcriptomic response to P. xylostella caterpillars and whether this interference is dependent on aphid density and time since aphid attack. Various JA-responsive genes were up-regulated in response to feeding by P. xylostella caterpillars. The additional presence of aphids, both at low and high densities, clearly affected the transcriptional plant response to caterpillars. Interestingly, some important modulators of plant defense signalling, including WRKY transcription factor genes and ABA-dependent genes, were differentially induced in response to simultaneous aphid feeding at low or high density compared with responses to P. xylostella caterpillars feeding alone. Furthermore, aphids affected the P. xylostella-induced transcriptomic response in a density dependent manner, which caused an acceleration in plant response against dual insect attack at high aphid density compared to dual insect attack at low aphid density. In conclusion, our study provides evidence that aphids influence the caterpillar-induced transcriptional response of A. thaliana in a density-dependent manner. It highlights the importance of addressing insect density to understand how plant responses to single attackers interfere with responses to other attackers and thus underlines the importance of the dynamics of transcriptional plant responses to multiple herbivory.